$$\begin{array}{rlll} 1. & \sim H \lor \sim G & \text{Premise} & \\ 2. & H\land (G\lor H) & \text{Premise} & \text{DEDUCE $F\& H$} \end{array}$$

Using the rules of inference from standard propositional logic, we have to deduce $F \land H$.

Well, if we can deduce $F \land H$, we can also deduce $F$ through simplification. That means that these two premises can imply any statement, $F$, ever.

It does not appear possible to deduce the conclusion.

I feel like the only thing we can deduce is $H \land \sim G$. I even thought of what appears to be a counterexample. Let

  • $H$: I live at home.

  • $G$: I own a piece of gold.

  • $F$: I own a Ferrari.

Premise 1 translates to "It is not the case that I live at home or it is not the case that I own a piece of gold." which is true. Premise 2 translates to "I live at home and either I own a piece of gold or I live at home." which is also true.

However, the conclusion $F \land H$ translates to "I own a Ferrari and I live at home", which is false.

(original scan of problem here)

  • 1
    $\begingroup$ Your analysis seems correct to me. $\endgroup$ Sep 5, 2013 at 2:05
  • 4
    $\begingroup$ You're right, assuming that the problem is stated correctly. $\endgroup$ Sep 5, 2013 at 2:07
  • $\begingroup$ You are right, but are these the only two assumptions given? There is nothing about $F$? $\endgroup$ Sep 5, 2013 at 2:09
  • 2
    $\begingroup$ Perhaps you should be discussing this with your professor, not with us... $\endgroup$
    – GEdgar
    Sep 5, 2013 at 2:26
  • 1
    $\begingroup$ what do you mean by "the rules of inference from standard propositional logic" each book has its own "the rules of inference from standard propositional logic" $\endgroup$
    – Willemien
    Sep 5, 2013 at 21:39

2 Answers 2


I suspect that Premise 1 is meant to be:
$ \lnot ( H \lor \lnot G ) $
which simplifies to:
$ \lnot H \land G $
and from which it follows, by and-ing to the simplification of Premise 2 as simply H:
$ H \land \lnot H \land G $
and then simply:
$ False $

From a falsehood, one can of course imply everything.


We do an abbreviated truth-table analysis.

The sentence $H\land (G\lor H)$ is true precisely if $H$ is true.

To make $\lnot H \lor \lnot G$ true it is enough to make $G$ false.

Thus (1) and (2) are simultaneously satisfiable by making $G$ false and $H$ true. They cannot therefore lead to a contradiction.

Remark: But the instructor could be right: it may be a mistake, not a typo.

  • $\begingroup$ If $H$ is false, then (2) is false.. $\endgroup$ Sep 5, 2013 at 2:14
  • $\begingroup$ Thanks! Had $G$ and $H$ transposed, $G$ comes before $H$. $\endgroup$ Sep 5, 2013 at 2:20
  • 1
    $\begingroup$ Hey guys, it was a mistake. The professor found the mistake after I emailed a second time. This thread is no longer necessary. $\endgroup$ Sep 5, 2013 at 4:25
  • $\begingroup$ @user2521987: Good work!${}{}{}{}{}$ $\endgroup$ Sep 5, 2013 at 4:34

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .